PEMBELAJARAN MENGONVERSI TEKS PANTUN MENJADI TEKS DIALOG DENGAN METODE GROUP INVESTIGATION (GI) - Suherman Suherman; Rahmat Widayat; Ika Mustika (JLER (Journal of Language Education Research), 2019)
This research is motivated by the difficulty of students learning to convert pantun texts into dialog texts. The purpose of this study are: (1) to know the activities of teachers and students when learning. (2) knowing student responses when learning. (3) knowing the difference in learning outcomes converting pantun text into dialogue text between the experimental class and the control class. The compiler wants to know the effectiveness of the Group Investigation (GI) method in learning to convert pantun text into dialog text. The study was conducted at Mahardhika Vocational School West Bandung 2016/2017 academic year. The research method used in this study is the experimental method. The experimental design used in this study was Quasi Experimental Design (Quasi Experimental Design). This study used the control class and the experimental class. The sample used in this study were students of class XI TKR1 and TKR class XI 2 students, each class amounted to 26 people. Based on the results of the analysis it can be concluded (1) teacher activities can be carried out as much as 90% and 91.7% students, (2) The response of students in learning to convert pantun texts into dialog texts with the 92.2% Group Investigation (GI) method, 3) Results the posttest value of the experimental class with the control class is different. The number of values obtained by the experimental class is 2,081 with an average value of 80.04, while the number of values obtained in the control class is 1,349 with an average value of 51.88.